2019
DOI: 10.3390/nano9040502
|View full text |Cite|
|
Sign up to set email alerts
|

Number Concentration of Gold Nanoparticles in Suspension: SAXS and spICPMS as Traceable Methods Compared to Laboratory Methods

Abstract: The industrial exploitation of high value nanoparticles is in need of robust measurement methods to increase the control over product manufacturing and to implement quality assurance. InNanoPart, a European metrology project responded to these needs by developing methods for the measurement of particle size, concentration, agglomeration, surface chemistry and shell thickness. This paper illustrates the advancements this project produced for the traceable measurement of nanoparticle number concentration in liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 23 publications
(28 reference statements)
0
33
0
Order By: Relevance
“…It is important to note that under the frame of the EU EMPIR project Innanopart, the number concentration data obtained for Au NP of very similar characteristics with spICP-MS and the DMF was demonstrated to agree well with that of reference techniques like Small Angle X-ray Scattering (SAXS). 10 This paper, 10 does not provide details on the systematic development and characterisation of the methodology discussed in the present work but describes a comprehensive comparison of a large set of data from several techniques developed by the EU consortium.…”
Section: Dynamic Mass Ow Methods For the Determination Of Tementioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that under the frame of the EU EMPIR project Innanopart, the number concentration data obtained for Au NP of very similar characteristics with spICP-MS and the DMF was demonstrated to agree well with that of reference techniques like Small Angle X-ray Scattering (SAXS). 10 This paper, 10 does not provide details on the systematic development and characterisation of the methodology discussed in the present work but describes a comprehensive comparison of a large set of data from several techniques developed by the EU consortium.…”
Section: Dynamic Mass Ow Methods For the Determination Of Tementioning
confidence: 99%
“…For objects of known geometries the latter can be converted to particle diameter, also providing information about the number-based size distribution of particles in the sample. SpICP-MS, unlike other particle counting techniques, 10 is also capable of measuring the dissolved fraction of the element within the same run provided that a fair distinction between the background and/or dissolved fraction and the nanoparticle fraction is achieved. [7][8][9] In spICP-MS analysis, in order to establish a relationship between the number of particle events detected over a dened analysis window (time scan) and the number of nanoparticles in solution, the NP TE must be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, consensus approaches to describing size distributions may be needed, e.g., DLS, SEM/TEM, field flow fractionation coupled to online sizing detectors, centrifugal techniques, nanoparticle tracking analysis and tunable resistive pulse sensing [ 50 ]. However, commonly the mean diameter is reported [ 84 , 92 , 93 ]. The structural representation of a NM must include size, size distribution, shape, and morphology distinguish one NM from another.…”
Section: Resultsmentioning
confidence: 99%
“…The pH measurements give an indication as to whether particles may be likely to undergo dissolution and transformation, this was not highlighted as a concern in this study where pH in the range of 4.3–8.2 was observed ( Table S2 ). It has been demonstrated that DLS and NTA methods can be highly reliable for monodisperse suspensions of spherical particles at appropriate concentrations ( Kestens et al, 2017 ; Langevin et al, 2018 ; Schavkan et al, 2019 ), such as the high purity Au NPs characterised here. However, the inherent lack of chemical specificity with light scattering analysis, and the fact that the NPs in the consumer products are typically present at low levels and in a complex mix, meant that their characterisation without prior treatment or separation, such as has been achieved with field flow fractionation ( Kammer et al, 2011 ), was not feasible.…”
Section: Discussionmentioning
confidence: 96%
“…The software requires the user to set a detection threshold value, which will influence the derived average particle size and number concentration. For the pure Au NP standard suspensions a value was selected such that the derived number concentration closely matched that determined by spICP-MS, which was identified as a reference method in a recent comparison study by Schavkan et al (2019) . This approach was not possible for the other samples analysed here due to the presence of large numbers of non-target particles and lack of chemical specificity of NTA analysis, therefore the selected threshold was based purely on the user's judgement.…”
Section: Methodsmentioning
confidence: 99%